Nagarjuna and the dialectic of conditioned origin - Gómez Fernández, Alfonso (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
The aim of this article is to expound the concept of «conditioned origin» (pratitya-samutpada) in the thought of Nagarjuna. This concept is the basis of his doctrine about vacuity, according to which all the things that exist are empty, insubstantial and lacking in their own nature, just because they have a dependent origin. So Nagarjuna destroys the traditional philosophical alternatives (based on excluding concepts) showing that the statement and the negation of these ideas are likewise flimsy. It is neither about the scepticism that abstains from every statement, nor about the philosophical nihilism. We are rather before the assertion that the fundamental reality is the insubstantial interdependence of all the phenomena. This is a subtle form of reality, the one between being and non-being, in the context of a relational and dialectic metaphysics.
Keywords: vacuity; space; movement; insubstantial; reality; scepticism; nihilism